EFFICIENCY REFUND LOAN PROGRAM SAVINGS AND LOANS OF WOMEN IN POVERTY REDUCTION IN DISTRICT NORTH ACEH DEWANTARA DISTRICT BY USING DATA ENVELOPMENT ANALYSIS (DEA) - Almuslim, Musrizal; Muttaqim, Hakim (JURNAL KEBANGSAAN, 2014)
This study aims to look at how efficiently the funds returns by groups Womens Savings and Loans (SPP) in the district of North Aceh district Dewantara. The sampling technique used in this study is purposive sampling. The data sample SPP Group amounted to 15 villages in the district Dewantara using secondary data sourced from the data report tuition refund loan through PNPM North Aceh district. DEA analysis results show efficiency of SPP Program Returns from 15 villages in the District Dewantara only Paloh Igeuh village which has reached 100% efficiency. Gadeng Paloh village, Paloh Pepper, western sassy, Tambon Baroh, Ulee pulo, Ulee reueleung, Sulu Geulumpang Timu and Tambon Baroh that the average value of its efficiency at 90% rate, while the Village of Bangka Jaya, Paloh rungkom still not efficient because the value in produced is below 70%, while the Village of Bangka Teubai, Geulumpang Timu, Keude Krueng Geukeuh show the efficiency rate between 80 percent to 89 percent of the necessary repairs in order to achieve 100% efficiency valueÂ Keywords : Data Envelopment Analysis (DEA), Womens Savings and Loans